Development of a Multicultural Curriculum to Enhance Student Tolerance in Senior High School - Sholeh, Muh Ibnu; Azah, Nur; Arifin, Zainur; Rosyidi, Hasyim; Sokip, Sokip; Syafi’I, Asrop; Sahri, Sahri (Sumber Belajar Sejahtera, 2024)
This study aims to explore how the development of a multicultural curriculum can enhance student tolerance at SMA Trenggalek. The main focus of the research is on the implementation of a multicultural curriculum that includes the integration of multicultural content into various subjects, extracurricular activities that support diversity, and specialized training for teachers. The research method employed is qualitative with a case study approach, involving school principals, teachers, students, and staff as research subjects. Data were collected through observations, in-depth interviews, and documentation. Data analysis was conducted thematically. The findings indicate that the implementation of a multicultural curriculum at SMA Trenggalek has a significant positive impact on students' attitudes towards tolerance. The integration of multicultural content in subjects such as Indonesian language and history helps students understand and appreciate cultural diversity and the nation's history. Extracurricular activities like cultural festivals and interfaith discussions serve as platforms for students to interact and learn firsthand about various cultures and beliefs. Additionally, intensive teacher training ensures that multicultural values are effectively applied in the teaching process. The impact of the multicultural curriculum is evident in the increased tolerance among students, the reduction of conflicts between students from different backgrounds, and the creation of a more inclusive learning environment. Students become more open to differences, reducing prejudice and stereotypes, and are more active in collaborating with peers from diverse backgrounds.